Epstein-barr virus infection in carcinoma of the salivary gland - Raab-Traub, N.; Rajadurai, P.; Flynn, K.; Lanier, A.P. (Faculty of Medicine, University of Malaya, 1996)
Undifferentiated carcinoma of the parotid gland contains clonal Epstein-Barr virus episomes without ladder arrays of restriction enzyme fragments representing virion DNA. Analysis of Epstein-Barr virus transcription in situ in parotid carcinoma specimens revealed that the EBER RNAs, latent membrane protein mRNA, and the BamHI-A rightward reading frame, BARF0, are expressed in the malignant epithelial cells.